A Cross-Country Analysis of the Determinants of Covid-19 Fatalities - Hideki Toya; Mark Skidmore (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Over the last year the world experienced the COVID-19 pandemic coupled with unprecedented policy responses. In this paper we examine the determinants of COVID-19 infections and fatalities in a cross-country analysis. We find that countries with greater income, less dense and greater elderly populations, fewer hospital beds, and more freedom experienced greater fatalities, and that travel restrictions and use of hydroxychloroquine reduced deaths. However, we find little evidence that lockdowns reduced fatalities, and though use of PCR testing resulted in more recorded infections, it was unassociated with fatalities.
Keywords: O10; O20; Q54; 330; pandemic; Covid-19; fatalities